2010
DOI: 10.1038/mp.2009.149
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the range of ZNF804A variants conferring risk of psychosis

Abstract: A trio of genome-wide association studies recently reported sequence variants at three loci to be significantly associated with schizophrenia. No sequence polymorphism had been unequivocally (P<5×10−8) associated with schizophrenia earlier. However, one variant, rs1344706[T], had come very close. This polymorphism, located in an intron of ZNF804A, was reported to associate with schizophrenia with a P-value of 1.6×10−7, and with psychosis (schizophrenia plus bipolar disorder) with a P-value of 1.0×10−8. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 45 publications
(53 reference statements)
6
125
1
2
Order By: Relevance
“…Consistent with previous studies (Riley et al, 2010;Williams et al, 2011;Steinberg et al, 2011;Zhang et al, 2011;Xiao et al, 2011, see Li et al, 2011, for an exception), the current study found evidence for the association between rs1344706 and schizophrenia. In addition, we replicated results of Walters et al (2010) that the association between rs1344706 and schizophrenia became stronger when the samples were limited to those with relatively high IQ.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with previous studies (Riley et al, 2010;Williams et al, 2011;Steinberg et al, 2011;Zhang et al, 2011;Xiao et al, 2011, see Li et al, 2011, for an exception), the current study found evidence for the association between rs1344706 and schizophrenia. In addition, we replicated results of Walters et al (2010) that the association between rs1344706 and schizophrenia became stronger when the samples were limited to those with relatively high IQ.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, an intronic SNP in this gene, rs1344706, has been found to be one of the most compelling candidate SNPs for schizophrenia. As shown by a recent whole genome study (O'Donovan et al, 2008) and several follow-up replications (Riley et al, 2010;Williams et al, 2011;Steinberg et al, 2011), there is a strong association between this SNP and schizophrenia with the A allele being the risk allele. This association has also been replicated among Han Chinese population in two studies Xiao et al, 2011) but not a third one .…”
Section: Introductionmentioning
confidence: 99%
“…Despite being relatively under-powered to replicate such a modest effect, two of three recently reported large SZ GWAS studies (Purcell et al, 2009;Sullivan et al, 2008) and a discrete replication study by Riley et al (2009) supported association between the same risk allele and increased SZ risk. Copy number variation at this locus has also been identified for psychosis (Steinberg et al, 2010). The protein encoded by ZNF804A is uncharacterized, but given its zinc finger domain, is likely to have a role in regulating gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…
Clinical symptomatology and the psychosis risk gene ZNF804A
Dear Editors,The single nucleotide polymorphism (SNP) rs1344706, mapping to the gene ZNF804A, has been implicated in schizophrenia susceptibility (O'Donovan et al 2008; International Schizophrenia Consortium, 2009;Stefansson et al 2009;Steinberg et al 2010). The original study reported stronger association when the phenotype was broadened to include bipolar disorder (p = 9.96 × 10 − 9 ) (O'Donovan et al 2008), but the variant is likely to have a modest effect on disease risk (OR = 1.12).
…”
mentioning
confidence: 99%